An Evaluation of a Trauma-Informed Intervention in Secure Juvenile Detention: The Impact on Youth-Level Incidents of Violence - Baetz, Carly Lyn (Criminal justice and behavior, 2025)
Few studies have examined the impact of trauma-specific interventions in juvenile justice settings, and juvenile justice-related outcomes are infrequently assessed. This study examined the impact of implementing youth skills groups (Skills Training in Affective and Interpersonal Regulation [STAIR]) and trauma training for staff (Think Trauma) on individual-level assaults in two secure detention facilities. The impact of the intervention was primarily evidenced in one facility among Black youth. In the same facility, the staff training (pre-skills groups) cohort and skills group cohort (post-staff training) evidenced a significantly greater reduction in violent incident rates as compared to the pre-intervention cohort. These findings highlight the importance of trauma-focused training for staff as a promising step toward reducing violence and improving staff members’ responses to a large subset of vulnerable youth.